Factors Influencing the Purchase of Two-Wheelers in Butwal Sub-Metropolitan City: A Consumer Perspective - Thapa, Mary (Devkota Journal of Interdisciplinary Studies, 2023)
The current research examined the determinants that impact the purchasing decisions of two-wheeler consumers in the Butwal region. The primary goal was to identify the critical independent variables that significantly influence the dependent variable of buying intentions, such as product knowledge, perceived quality, perceived value, and perceived risk. Using multiple regression and correlation analysis, the study found that purchasing intentions are significantly influenced by perceived value and quality. This established a substantial and significant correlation. Conversely, no statistically significant correlation was found between variables including product knowledge and diminished perceived risk and the purchasing decisions of consumers. To gain a competitive advantage in the market, companies operating in the Butwal two-wheeler sector should place a high priority on improving the perceptions of quality and value held by potential customers.